Structural Phase Transition Studies on PMN-0.35PT using Infrared Spectroscopy - Araujo, E. B. [UNESP]; Guarany, C. A. [UNESP]; Yukimitu, K. [UNESP]; Moraes, João Carlos Silos [UNESP]; Hernandes, A. C. (Taylor & Francis Ltd, 2008)
The purpose of the present work is to report studies on structural phase transition for PMN-xPT ferroelectric, with melt PbTiO3 composition around the MPB (x = 0.35 mol %), using infrared spectroscopy technique. The study was centered on monitoring the behavior of the 1-(NbO), 1-(TiO) and 1-(MgO) stretching modes as a function of temperature. The increasing as a function of temperature for 1-(TiO) and 1-(MgO) modes, observed between 230 and 300 K, can be related to the monoclinic (MC) + tetragonal (T) phase coexistence in the PMN-PT.
Keywords: Ferroelectric; PMN-PT; monoclinic phase